Effects of Univalent Cations on the Activity of Particulate Starch Synthetase - Nitsos, Ronald E. (1969)
An investigation was made to determine the univalent cation requirements of starch synthetase from a variety of plant species of economic importance. The particulate enzyme from sweet corn was shown to have an absolute requirement for potassium, with the optimum activation occurring at 0.05 M KCl. Rubidium, cesium, and ammonium were 80% as effective as potassium while sodium and lithium were respectively 21% and 8% as effective as potassium. The K(A) for potassium was determined to be 6 mM. In the case of the particulate starch synthetase from wheat, bush beans, field corn, soybeans, peas, or potatoes, considerable stimulation of enzyme activity was obtained by the addition of potassium to the reaction mixture. In these studies, low enzyme activity was observed in the absence of added potassium, but the content of endogenous univalent cations in the reactions may be sufficient to account for the activities observed. Anions of various types had no effect on starch synthetase activity. Divalent cations produced slight activation in the presence or absence of potassium. All efforts to show a potassium requirement for glycogen synthetase from rat liver have been negative.